An end-to-end test for MR-guided online adaptive radiotherapy - Hoffmans, Daan; Niebuhr, Nina Isabelle; Bohoudi, Omar; Pfaffenberger, Asja; Palacios, Miguel (Physics in medicine and biology, 2020)
In the evolving field of adaptive MR guided radiotherapy, the need for dedicated procedures for acceptance and quality assurance is increasing. Research has been devoted to MR compatible dosimeters and phantoms, but to date no end-to-end test has been presented that covers an MRgRT workflow. Such an end-to-end test should comprise each step of the workflow and include all associated uncertainties. The purpose of this study was to investigate the usability of an anthropomorphic deformable and multimodal pelvis (ADAM-pelvis) phantom in combination with film dosimetry for end-to-end testing of an MRgRT adaptive workflow. The ADAM-pelvis phantom included surrogates for muscle tissue, adipose and bone, as well as deformable silicone organs mimicking a prostate patient. At the interfaces of the critical structures (bladder and rectum), small pieces of GafChromic EBT3 films were placed to measure delivered dose. Pre-treatment MR imaging of the phantom was used to delineate the prostate, rectum and bladder and to generate a treatment plan to deliver 2 Gy to the prostate. Electron density (ED) map from CT imaging was used for dose calculation after deformable image registration (DIR) to the pre-treatment MR scan. At each fraction, bladder- and rectum filling was varied and a new adapted plan was generated. Dose calculation was performed using both a DIR-based ED map and a CT-based ED map after acquisition of a new CT scan of the phantom at each fraction. All dose calculations were performed taking into account the magnetic field. A good agreement between measured and calculated dose was found using both, the CT-derived and the DIR-based ED map (2.0% and 2.8% dose difference, respectively). The gamma index pass-rate (3%/2 mm) varied from 96.4% to 100%.The ADAM-pelvis phantom was suitable for end-to-end testing in MR-guided radiotherapy and a very good agreement with the calculated dose was achieved.
Gesehen am 06.08.2020